Magnetically active elastomers: ferromagnetic particles under conditions of restricted freedom - Raikher, Yu.L.; Vaganov, M.V. (Perm Federal Research Centre Journal, 2021)
The article communicates certain results of research work carried out in 2017–2019. On the one hand, the authors didn’t aim at going too deep into details; on the other hand, they didn’t want to completely sacrifice physical rigour in favour of comprehensibility. For this reason, the origina part is preceded by an introductory one (sections 1–3) that gives to an unprofessional reader a minimally sufficient amount of information on classical single-domain particle physics. It is also worth noting that the article for the first time presents in Russian the scientific materials that earlier were published only in international journals.